Determinant of gold investment decision in Z generation: a study of planned behavior and social learning theory / Endang Sulistiyani ... [et al.] - -, Endang Sulistiyani; -, Sri Wahyuni; -, Dody Setyadi; -, Karnowahadi; -, Rustono (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
This study was conducted to analyze the determinant of gold investment decision by exploring the theories of planned behavior and social learning, with the model incorporating locus of control as a mediating variable. The respondents were Z generation gold investors of PT Pegadaian in Semarang City, Central Java, Indonesia. A purposive sampling method was used and Z generation selected digital gold investment as the preferred instrument. To achieve this preference, gold bullion was purchased as a means of savings, effectively eliminating the necessity for physical storage, and the data were collected through questionnaires, observations, and interviews. Subsequently, the collected data were subjected to analysis using structural equation modeling and the validity of the mediating variables was assessed using Sobel test. The results showed that there were direct and indirect influences of personal selling and financial literacy variables on locus of control and gold investment decision. However, online customer review (OCR) did not have a direct or indirect influence on the variable. In addition, financial literacy had a direct and indirect influence on investment decision through locus of control.